2015
DOI: 10.1128/jvi.00521-15
|View full text |Cite
|
Sign up to set email alerts
|

Equine and Canine Influenza H3N8 Viruses Show Minimal Biological Differences Despite Phylogenetic Divergence

Abstract: The A/H3N8 canine influenza virus (CIV) emerged from A/H3N8 equine influenza virus (EIV) around the year 2000 through the transfer of a single virus from horses to dogs. We defined and compared the biological properties of EIV and CIV by examining their genetic variation, infection, and growth in different cell cultures, receptor specificity, hemagglutinin (HA) cleavage, and infection and growth in horse and dog tracheal explant cultures. Comparison of sequences of viruses from horses and dogs revealed mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 77 publications
0
41
1
2
Order By: Relevance
“…These results are in agreement with the findings presented in here. Feng et al showed that inoculation of both viruses into tracheal explants yielded similar levels of infection by each virus in dog tracheas, whereas equine viruses were more infectious than canine viruses in horse tracheas (27). However, in our experiments with pig trachea explants, the replication of Eq and Ca virus strains was minimal (Tables 3 and 4), indicating that factors other than sialic acid binding may play a role in infectivity and host susceptibility.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…These results are in agreement with the findings presented in here. Feng et al showed that inoculation of both viruses into tracheal explants yielded similar levels of infection by each virus in dog tracheas, whereas equine viruses were more infectious than canine viruses in horse tracheas (27). However, in our experiments with pig trachea explants, the replication of Eq and Ca virus strains was minimal (Tables 3 and 4), indicating that factors other than sialic acid binding may play a role in infectivity and host susceptibility.…”
Section: Discussioncontrasting
confidence: 49%
“…Also, they were the ones with lower binding values to pig trachea explants and therefore the ones exhibiting the lowest values of viral replication (Tables 3 and 4). Recent results from Feng et al (27) analyzing other related H3N8 canine and equine viruses indicated that canine and equine viruses show minimal biological differences despite phylogenetic divergence. In fact, both virus types bind more effectively to ␣-2,3-linked sialic acid than to ␣-2,6-linked sialic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant wild-type (WT) and live-attenuated (LACIV) H3N8 CIVs were generated using A/canine/ NY/dog23/2009 H3N8 plasmid-based reverse genetics techniques (72) and grown in MDCK cells at 33°C. Influenza A/Ca/IL/41915/2015 H3N2 was also grown in MDCK cells at 33°C.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…We utilized EIV isolates sampled close to the ancestor CIV, starting from 1990 to 2013, and CIV isolates sampled soon after the emergence in dogs, from 2004 to 2013. Sequence alignments and the generation of consensus sequences were performed as described previously (15). …”
Section: Methodsmentioning
confidence: 99%
“…We therefore sought to examine these proteins for functional differences by comparing gene suppression ability using reporter gene assays and by evaluating the details of their influence on host gene expression through RNA sequencing (RNA-seq). CIV emerged from EIV around 2000, and since then it has fixed a unique set of mutations in all its genes, including PA-X (15). By evaluating the biology of the two PA-X proteins we sought to further define PA-X function and to gain a better understanding of virus evolution and adaptation.…”
Section: Introductionmentioning
confidence: 99%